Handbook of Optimization in Telecommunications - Resende, Mauricio G.C; Pardalos, Panos M. (Springer US : Imprint: Springer, 2006)
"I highly recommend The Handbook of Optimization in Telecommunications as an invaluable resource for anyone interested in understanding the impact of optimization on the most import problems facing the telecommunications industry today. The handbook is unprecedented in the breadth and depth of its coverage, illustrating that telecommunications offers a vast array of interesting and important optimization problems probably exceeding the traditional areas of transportation networks, engineering, economics and military operations." -Clyde Monma, Retired Chief Scientist, Applied Research Area, Telcordia Technologies Telecommunications has had a major impact in all aspects of life in the last century. There is little doubt that the transformation from the industrial age to the information age has been fundamentally influenced by advances in telecommunications. Optimization problems are abundant in the telecommunications industry. The successful solution of these problems has played an important role in the development of telecommunications and its widespread use. Optimization problems arise in the design of telecommunication systems and in their operation. The Handbook of Optimization in Telecommunications brings together experts from around the world who use optimization to solve problems that arise in telecommunications. The editors made an effort to cover recent optimization developments that are frequently applied to telecommunications. The spectrum of topics covered includes planning and design of telecommunication networks, routing, network protection, grooming, restoration, wireless communications, network location and assignment problems, Internet protocol, World Wide Web, and stochastic issues in telecommunications. The editors' objective is to provide a reference tool for the increasing number of scientists and engineers in telecommunications who depend upon optimization in some way. Each chapter in the handbook is of an expository nature, but of scholarly treatment, and includes a brief overview of the state-of-the-art thinking relative to the topic, as well as pointers to the key references in the field. Specialists as well as nonspecialists should find this handbook stimulating and helpful. Audience This handbook will be useful for students, researchers, and practitioners in engineering, computer science, statistics, operations research, and mathematics.